Comuneros y talamontes: cooperación y conflicto en la devastación del bosque, en Cherán, Michoacán (2006-2011) (2021)
During five years (2006-2011), the forest of the indigenous community of Cherán, located in the state of Michoacán, Mexico, suffered a destruction process that ended with about 70% of the timber area. During this period, a series of associations were formed between local and foreign actors involved in illegal logging (loggers) and in the defense of the territory (comuneros). The purpose of this article is to provide a dense description of the process of figuration between comuneros and loggers in these years. The main argument is that, far from forming dichotomous relationships between the two groups, there were a series of connections that oscillated between cooperation and conflict. The analytical framework follows the sociological proposal of Norbert Elias with respect to the concept of figuration. The methodology is qualitative and was developed through ethnographic fieldwork.